The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fphar.2013.00168
|View full text |Cite
|
Sign up to set email alerts
|

Efflux pumps of Gram-negative bacteria: what they do, how they do it, with what and how to deal with them

Abstract: This review discusses the relationship of the efflux pump (EP) system of Gram-negative bacteria to other antibiotic resistance mechanisms of the bacterium such as quorum sensing, biofilms, two component regulons, etc. The genetic responses of a Gram-negative to an antibiotic that render it immune to an antibiotic are also discussed. Lastly, the methods that have been developed for the identification of bacteria that over-express their EP system are presented in detail. Phenothiazines are well-known antipsychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 93 publications
3
80
0
2
Order By: Relevance
“…Studies have shown that targeting the efflux pump system could obviate other resistance mechanisms and reverse multidrug resistance, thus restoring the efficacy of antibiotics [24]. In this study, we observed that susceptibility to ertapenem, doripenem, and tigecycline was increased two-to fourfold in the presence of CCCP (Table 2); we also found that non-susceptibility to ertapenem, doripenem, and tigecycline was completely abolished in 24%, 37.3%, and 48% of the isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that targeting the efflux pump system could obviate other resistance mechanisms and reverse multidrug resistance, thus restoring the efficacy of antibiotics [24]. In this study, we observed that susceptibility to ertapenem, doripenem, and tigecycline was increased two-to fourfold in the presence of CCCP (Table 2); we also found that non-susceptibility to ertapenem, doripenem, and tigecycline was completely abolished in 24%, 37.3%, and 48% of the isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is the special feature of some efflux protein transporter. A case of the last co-operation is that of reserpine and Bmr protein, an individuals from MFS transporters that is responsible for tetracycline efflux in Bacillus subtilis 19 .…”
Section: Efflux Pump Inhibitor Originate From Plantmentioning
confidence: 99%
“…One escape strategy is the p odu tio of deg adatio e z es su h as β-lactamases, rendering the antibiotic inactive due to hydrolysis of the β-lactam pharmacophore (Bush 2010;Rawat and Nair 2010). Alternatively, several Gram-negative pathogens overexpress membrane-embedded efflux pumps, which actively transport drugs out of the bacteria (Amaral et al 2014;Blair et al 2014). Therefore, considerable efforts have been made to esto e the a ti a te ial a ti it of β-lactams against Gramnegative pathogens through inhibition of β-lactamases or of efflux pumps.…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 99%